Effect of perforated twisted-tapes with parallel wings on heat tansfer enhancement in a heat exchanger tube - C. Thianpong; P. Eiamsa-ard; P. Promvonge; S. Eiamsa-ard (My University, 2012)
This article reports an experimental investigation on heat transfer and pressure drop characteristics of turbulent flow n a heating tube equipped with perforated twisted tapes with parallel wings (PTT) for Reynolds number between 500 and 20500. The design of PTT involves the following concepts: (1) wings induce an extra turbulence near tube all and thus efficiently disrupt a thermal boundary layer (2) holes existing along a core tube, diminish pressure losswithin the tube. The parameters investigated were the hole diameter ratio (d/W = 0.11, 0.33 and 0.55) and wing depthratio (w/W = 0.11, 0.22 and 0.33). A typical twisted tape was also tested for an assessment. Compared to the plain ube, the tubes with PTT and TT yielded heat transfer enhancement up to 208% and 190%, respectively. The valuation of overall performance under the same pumping power reveal that the PTT with d/W = 0.11 and w/W = .33, gave the maximum thermal performance factor of 1.32, at Reynolds number of 5500. Empirical correlations of he heat transfer, friction factor and thermal performance for tubes with PTTs were also developed. In addition, the wirling/axial flow patterns of tube with PTT were visualized using dye injection technique.
Keywords: Heat transfer enhancement; Heat Transfer Mechanisms